Sustainable lactic acid production from agricultural waste: a review of current techniques, challenges and future directions - Nurasyikin Abdul Rahman; Zainab Ngaini; Saba Farooq; Sabrina Chua Ai Ling; Puteri Nabilah Jefree Shahren (Bioresources and Bioprocessing)
Abstract The increasing demand for lactic acid (LA), driven by its applications in biodegradable plastics, food additives, pharmaceuticals, and cosmetics, necessitates the development of sustainable production methods. Traditional processes often rely on food-based feedstock, aggravating food security concerns. This review addresses the critical gap in utilising agricultural waste as a non-food feedstock for LA production, thereby reducing waste and promoting a circular economy. Current techniques are thoroughly explored, including fed-batch, batch, and continuous fermentation procedures, as well as the utilisation of various microbial strains, including Lactobacillus species. Recent developments in genetic engineering and innovative fermentation techniques are discussed, alongside challenges such as substrate variability and contamination. By highlighting the potential of agricultural residues, such as sugarcane bagasse, rice husk and corn stover, this review provides a roadmap for future research and industrial applications to enhance sustainability and efficiency in LA production.